Radiolysis of methyl alcohol water solution by pulsed electron beam; Korus 2004; V. 2 - Urazbahtina L. R.; Remnev G. E. Gennady Efimovich; Goncharov D. V.; Pushkarev A. I. Aleksandr Ivanovich (2004, 2004)
In the work the experimental data on electron beam influence with the energy up to 500 keV on the methanol water solution are presented. The investigations were executed using real industrial water. The methanol content in water before and after irradiation was analyzed by the chemical method and with the help of gas-liquid chromatograph. The decomposition rate estimation of methanol water solution in the dose interval from 5 up to 20 MRad depending on the absorber layer thickness was carried out.